Taṭwīr Mawād at-Tarākīb Fī Kitāb al-Lughah al-`Arabiyah al-Madrasī Kurikulum 2013 Bi Microsoft Powerpoint - Raudhatul Jannah; Zulhelmi Zulhelmi (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
The title of this research is the Development of Material Structure in Arabic Textbook 2013 Curriculum year, with Microsoft PowerPoint. The researcher chose this title because she saw as the students of SMP Muhammadiyah 1 Banda Aceh, in practicing Arabic they did not pay attention to the correct language principles. Especially when they practiced Arabic sentences that do not match verbs and personal pronouns be right. In this school the students really like learning by using media, this phenomenon can be seen from the student questionnaire that they were very enthusiastic about learning by using PowerPoint. Therefore, the researcher wants to develop structural material using PowerPoint. The purpose of this research is to develop a product for the development of the material structure to determine the effectiveness of the material by using PowerPoint, and to find out what the experts think about the development of material structure using PowerPoint media. For data collection, the researcher used a pretest and post-test question questionnaire and an expert observation sheet. The results of the research show that the use of Microsoft PowerPoint media in developing the material structure increases student ability in learning structure so the media is effective for teachers in increasing their ability to learn it. Based on the results of the post-test average score (T-test 2,09 <7,1> 2,86.) this value shows that the development of material structure by using PowerPoint media at SMP Muhammadiyah 1 Banda Aceh is effective and useful. As for the expert assessment, it shows that the product is accepted based on the expert observation value, namely 80% from Expert I, and 75% from Expert II